2008
DOI: 10.1111/j.1528-1167.2008.01580_1.x
|View full text |Cite
|
Sign up to set email alerts
|

Traditional healers and epilepsy treatment on the Kenyan coast

Abstract: From 2005-2007, we addressed problems of access to epilepsy care in Kilifi, Kenya from an anthropological perspective. Researchers have identified a lack of attention to contextual constraints on treatment decision-making (Garro, 1998, p. 321; Good, 1986, p. 164). Few studies have examined the social and procedural factors that shape and constrain the treatment choices for epilepsy, such as the roles of providers in the community and the structural differences between biomedical and alternative treatments. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…Triangulating our results with focus group discussion, observations and surveys could have been used to increase validity of our data. However, the high agreement in our respondents and the patterns of results closely mirroring earlier disease-specific studies (such as those by Kendall-Taylor [11] , [12] and Mwenesi [30] ) attest to the validity of both our data and our conclusions. Further study of the potential influence of socio-demographic aspects e.g.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Triangulating our results with focus group discussion, observations and surveys could have been used to increase validity of our data. However, the high agreement in our respondents and the patterns of results closely mirroring earlier disease-specific studies (such as those by Kendall-Taylor [11] , [12] and Mwenesi [30] ) attest to the validity of both our data and our conclusions. Further study of the potential influence of socio-demographic aspects e.g.…”
Section: Discussionsupporting
confidence: 91%
“…Previous research in Africa has investigated parental perceptions of the aetiology of different diseases, and their health-seeking behaviour. The focus has largely been on describing socio-cultural determinants of health-seeking behaviour in the context of specific health conditions; but these studies have largely focussed on malaria [8] , [9] , malnutrition [5] , [10] and epilepsy [11] [13] . However, there is a need to take a non-disease-specific perspective, since in certain cases some health-related beliefs and practices may be pervasive and may influence health-seeking behaviour in different contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Failure to observe these traditions could have repercussions possibly leading to a curse that could result into ASD. Studies conducted in Kenya have shown that preferences are given to traditional healers in treatment of epilepsy and disability because these conditions are believed to be caused by evil powers [ 21 , 22 ]. Traditional healers are believed to be well placed in treating calamities associated with cultural beliefs and practices.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding determinants of traditional healer utilization in this context is warranted as the cultural understanding of epilepsy has been shown to be an important determinant in care-seeking behavior [ 29 ]. Identifying ways of working with traditional healers to reduce the epilepsy treatment gap, however, may be more productive than attempting to change individual’s behavior.…”
Section: Discussionmentioning
confidence: 99%